2021
DOI: 10.3389/fsufs.2021.721840
|View full text |Cite
|
Sign up to set email alerts
|

Plant Nitrogen Uptake From Insect Frass Is Affected by the Nitrification Rate as Revealed by Urease and Nitrification Inhibitors

Abstract: Insect protein production is considered a sustainable alternative to livestock protein which furthermore utilizes waste streams. Its production can have positive but also potentially negative environmental effects, which require evaluation. Frass, the byproduct of insect production, is regarded an efficient organic fertilizer or soil amendment. However, several studies report negative frass effects on plant growth and nitrogen (N) cycling. Therefore, a pot trial was carried out which sought to understand N rel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 49 publications
1
6
1
Order By: Relevance
“…This suggests that phytotoxicity could be due to oxidizable compounds, such as NH 4 , and/or adsorbable on organic matrices (Hénault-Ethier 2020). Higher concentrations of mealworm frass (3% w/w) were associated with the inhibition of ryegrass seedling germination, possibly due to ammonia or salinity (Watson, Preißing and Wichern 2021).…”
Section: Phytotoxicity Potential Of Frassmentioning
confidence: 99%
See 1 more Smart Citation
“…This suggests that phytotoxicity could be due to oxidizable compounds, such as NH 4 , and/or adsorbable on organic matrices (Hénault-Ethier 2020). Higher concentrations of mealworm frass (3% w/w) were associated with the inhibition of ryegrass seedling germination, possibly due to ammonia or salinity (Watson, Preißing and Wichern 2021).…”
Section: Phytotoxicity Potential Of Frassmentioning
confidence: 99%
“…BSF frass also seem to be a fast-acting fertilizer, with most N present in an organic form, and a variable ammonia content (Elissen, van der Weide and Gollenbeek 2023). The uptake of frass Nitrogen by plants is affected by the nitrification rate (Watson, Preißing and Wichern 2021). Frass can also affect soil pH, which in turn can influence bacterial activity and bioavailability of nutrients and minerals (Choi and Hassanzadeh 2019).…”
Section: Fertilizing Values Of Frassmentioning
confidence: 99%
“…The very limited studies available to date have shown that the application of frass increases yield (Rosmiati et al, 2017;Houben et al, 2020Houben et al, , 2021, activates plant defense responses against abiotic (Poveda, 2021) and biotic stress (Quilliam et al, 2020), and improves soil microbial activities (Gebremikael et al, 2020). On the contrary, few other studies found negative effects of BSF frass and other commercially available frass on soil quality and plant growth, such as phytotoxicity (Alattar et al, 2016;Watson et al, 2021a,b) and excessive nitrite accumulation in soil (Watson et al, 2021a).…”
Section: Introductionmentioning
confidence: 99%
“…Frass are the secondary material generated by insect-based waste management system. They consist of a nutrient rich material that, whether not correctly handled, may results in an important source of environmental impact 43 , 44 . Current practices include use of the frass as soil conditioner/fertilizer in agriculture.…”
Section: Discussionmentioning
confidence: 99%